Design of The Population Information System in The Village of Pajajaran - Irvan Nugraha; Falaah Abdussallam (Journal of Applied Engineering and Technological Science (JAETS), 2022)
Population or demography is the study of the dynamics of the human population. Demographics includes the size, structure and distribution of a population, and how the population changes over time as a result of births, deaths, migration, and aging. The current population system is still using the manual method, namely using the form provided by the Pajajaran Village, which is deemed less effective and efficient, therefore, there are often miscalculations of the number of residents when reporting to the Cicendo District, Bandung City. This study aims to analyze and design a population system. The design of this population information system uses PHP Native programming and MySQL Database Management System. With the existence of a web-based information system, it is hoped that it will facilitate the making of valid and not fictitious population reports